Microstructure, sintering behavior and microwave dielectric properties of the Mn-doped TiP2O7. Issue 9 (November 2015) - Wang, Y.N.; Chen, H.Z.; Bian, J.J.
Abstract: The effects of Mn-doping and sintering atmosphere on the phase constituent, sintering behavior, and microstructure of TiP2 O7 have been investigated by XRD, SEM, EDS and XPS analyses. Microwave dielectric properties of the Mn-doped TiP2 O7 ceramics were also studied with a network analyzer in the frequency range 10–13 GHz. A certain amount of Mn-doping could efficiently hinder the appearance of (TiO)2 P2 O7 impurity phase, but led to the formation of Mn0.5 Ti2 (PO4 )3 type secondary phase instead. The substitution of Mn for Ti was controlled by the diffusion process and only took place in Mn0.5 Ti2 (PO4 )3 phase and the neighbored matrix phase. Their composition can be identified as Mn0.5 Ti2− x Mn y (PO4 )3 and Ti1− x Mn x P2 O7 . Although single phase ceramics could not be obtained, the introduction of small amount of MnO2 remarkably improved the sinterability and microwave dielectric properties. Dense microstructure and good optimized microwave dielectric properties with ε r ~14, Q × f ~87, 304 GHz, and τ f ~−19 ppm/°C could be obtained for x =0.05 composition after sintering at 1200 °C/2 h in air. The effect of O2 atmosphere during sintering on the above properties of the Mn-doped samples has also been investigated. The amount of Mn0.5 Ti2− x Mn y (PO4 )3 impurity phase decreased considerably for the specimen sintered in O2 atmosphere compared with that sintered in air, however, which has little effect on the microwave dielectric properties.